2022
DOI: 10.5267/j.uscm.2022.2.017
|View full text |Cite
|
Sign up to set email alerts
|

Green supply chain management and competitive advantage: The mediating role of organizational ambidexterity

Abstract: This study develops a research framework to study the impact of green supply chains with three dimensions, namely green purchasing, green manufacturing, and green marketing to achieve competitive advantage with the existence of organizational ambidexterity as a mediating variable in Jordanian industrial companies. The study targeted the most important Jordanian industrial companies, which included 46 industrial companies out of 66 companies listed on the Amman Stock Exchange. The researchers personally adminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(21 citation statements)
references
References 1 publication
5
12
0
Order By: Relevance
“…Hence, we expect not just a direct impact of SCA on OP but also an indirect effect of SCA in the BI-OP relationship. This finds support from prior studies (Aljumah et al, 2021;Pertheban and Arokiasamy, 2019;Chams-Anturi et al, 2019;Belhadi et al, 2021;Zhao et al, 2021;Al-khawaldah et al, 2022), which indicated that organizational ambidexterity plays an indirect role in improving the performance of firms. This study based on the contradictory views expressed re-examines the relationship by posing the third and fourth hypotheses.…”
Section: Effect Of Business Intelligence On Operational Performancesupporting
confidence: 82%
“…Hence, we expect not just a direct impact of SCA on OP but also an indirect effect of SCA in the BI-OP relationship. This finds support from prior studies (Aljumah et al, 2021;Pertheban and Arokiasamy, 2019;Chams-Anturi et al, 2019;Belhadi et al, 2021;Zhao et al, 2021;Al-khawaldah et al, 2022), which indicated that organizational ambidexterity plays an indirect role in improving the performance of firms. This study based on the contradictory views expressed re-examines the relationship by posing the third and fourth hypotheses.…”
Section: Effect Of Business Intelligence On Operational Performancesupporting
confidence: 82%
“…Lean supply chains are essential for contemporary organizations, and they aim at quick and effective response to changing customers' needs (Alshawabkeh et al, 2022;Green et al,2019), by dealing with the unsteady demands and short product life cycles, and by responding to delivery requests in terms of quantity, quality and speed (Al-khawaldah et al, 2022;Inman, & Green,2021). They are all the activities and processes that help in maintaining the flow of goods, services, information, and money from the moment they are produced to the moment of their consumption and contribute to reducing costs and wastes and meeting the needs of customers (Ikumapayi et al, 2020).…”
Section: Lean Supply Chainsmentioning
confidence: 99%
“…The fourth industrial revolution is a result of integrating supply chains into information and telecommunication technologies (Al-Nawafah et al, 2022;Al-khawaldah et al, 2022;Ghadge et al, 2020;Sharma et al, 2021). Since digitization is an important component of the success of supply chains in the current business environment, companies seek to adopt and use industry 4.0 technologies.…”
Section: Introductionmentioning
confidence: 99%